2021
DOI: 10.21203/rs.3.rs-422622/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The protective role of propolis against multi heavy metals-induced oxidative stress-hepato-renal damage in the male of albino rats

Abstract: The study was designed to clarify the hepato-renal protective effects of propolis extract against heavy metals-induced toxicity via oral administration to the males of albino rats. Lead (Pb), Nickel (Ni), Cadmium (Cd), and Antimony (Sb) are toxic heavy metals have the ability to produce reactive radicals in the biological systems causing public and animals health hazards through disrupting balances between pro-oxidant and antioxidant defense system, resulting in excessive reactive oxygen species (ROS) producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…According to Abu-Almaaty et al [ 40 ] and El-Amawy et al [ 41 ], propolis has a protective effect on different organs of albino rats due to its antioxidant function against oxidative stress caused by heavy metals; moreover, propolis improved the histopathology and the morphometry of the testicular tissues in groups treated with propolis-containing diets. Hashem [ 42 ] studied the preventive properties of propolis against testicular damage caused by carbon tetrachloride (CCl 4 ) and found that propolis increased testosterone levels while decreasing oxidant levels.…”
Section: Resultsmentioning
confidence: 99%
“…According to Abu-Almaaty et al [ 40 ] and El-Amawy et al [ 41 ], propolis has a protective effect on different organs of albino rats due to its antioxidant function against oxidative stress caused by heavy metals; moreover, propolis improved the histopathology and the morphometry of the testicular tissues in groups treated with propolis-containing diets. Hashem [ 42 ] studied the preventive properties of propolis against testicular damage caused by carbon tetrachloride (CCl 4 ) and found that propolis increased testosterone levels while decreasing oxidant levels.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, propolis is a natural material that contains phenolic and flavonoid chemicals, which have been found to be able to be a scavenger for free radicals, keeping lipids and other molecules away from oxidative damage and inhibiting lipid peroxidation [10] . Propolis action was thought to be by different mechanisms including chelation or antagonism of heavy metals in order to decrease their production of free radicals, counteracting their oxidative effect and interfering with the reaction of auto-oxidative chain [11] .…”
Section: Introductionmentioning
confidence: 99%